KOMPARASI ALGORITMA C4.5 DAN NAIVE BAYES UNTUK MENGANALISA KELAYAKAN PENGAJUAN KREDIT - Siti Nur Khasanah (Jurnal Mantik Penusa)
In determining the credit worthiness of a customer, a method is needed so that the results of the assessment carried out by the credit analysis department are accurate, so that the applicant can be predicted whether it will become a customer with a smooth or problematic payment. In this study, two algorithms were compared, namely the C4.5 algorithm and Naive Bayes. The algorithm will be applied to credit payment data labeled current and problematic customers. From the research results, the accuracy of the C4.5 algorithm is 87.62% while the accuracy obtained for the Naive Bayes algorithm is 90.00%. So it can be concluded, in this study that the Naive Bayes algorithm has higher accuracy than the C4.5 algorithm.